BUKU DATA DAERAH IRIGASI CILACA Studi Kasus Kegiatan Magang di Dinas Bina Marga, Sumber Daya Air, Energi, dan Sumber Daya Mineral Kabupaten Cilacap - , GUNAWAN MULIA AJI, Suwardo, ST., MT., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lack of Operation and Maintenance of Irrigation Network in the field one problem is the absence of data in an Irrigation Network itself. Therefore formulated The Data Book of Cilaca Irrigation Area is a complete record of irrigation area design Cilaca and based from record inventory which can be used as a code execution of Operation and Maintenance daily irrigation network for Machanician and Irrigation Maintainer ( Agency, UPTD, Machanician of Irrigating ) and for The Field Operation or Network Organizer or Irrigation especially in Irrigation Areas of Cilaca. Purpose of preparation The Data Book of Cilaca Irrigation is available data on Irrigated Areas which can be used to Activity Operation and Maintenance Network Irrigation, repair, establishment of network irrigation. Observations in the field, interview, checks and repair written record of the previous year is an appropriate method to obtain accurate data from an Irrigated Areas.